Hambatan Mesenchymal Stem Cell Terhadap Proliferasi Limfosit T - Sofia Fajarwati (Jurnal Biosains Pascasarjana, 2018)
AbstractMesenchymal stem cells (MSCs) are a kind of stem cells that can differentiate into several kinds of mesodermal cell decent. MSCs can be cultured in vitro therefore it can serve many purposes. However, MSCs also have immunosuppresion effects, one of the way is by suppresing T cell proliferation. MSCs need cell-to-cell contact with activated T cells in certain rasio to release it’s surppresion properties. Primery help from inflamatory cytokines is also needed. MSCs’s suppresion effect can be mediated by several molecules such as indoleamine 2,3-dioxygenase (IDO), inducible nitric-oxide synthase (iNOS), prostaglandin E2 (PGE2), transform growth factor-β (TGF-β), hepatocyte growth factor (HGF), and HLA-G5 soluble. MSCs’s characteristic and culture conditions can affect clinical applications.Keywords: Mesenchymal stem cells, T cell proliferation, immunosuppresion AbstrakMesenchymal stem cells (MSC) adalah salah satu jenis stem cell yang dapat berdiferensiasi menjadi beberapa macam turunan sel mesodermal. MSC dapat dikembangkan secara in-vitro sehingga memiliki banyak kegunaan. Namun, MSC juga dapat memberikan beberapa efek imunosupresi, salah satunya dengan cara menekan proliferasi sel T. Untuk melakukan supresi, MSC memerlukan kontak cell-to-cell dengan sel T teraktivasi dengan rasio tertentu. MSC juga membutuhkan bantuan awal dari sitokin inflamasi. Efek supresi MSC dapat diperantarai oleh beberapa molekul seperti indoleamine 2,3-dioxygenase (IDO), inducible nitric- oxide synthase (iNOS), prostaglandin E2 (PGE2), transform growth factor-β (TGF-β), hepatocyte growth factor (HGF), dan HLA-G5 terlarut. Sifat dan kondisi biakan MSC dapat mempengaruhi aplikasi klinis.Kata kunci: Mesenchymal stem cells, proliferasi sel T, imunosupresi